STRATEGI GURU DALAM PEMBELAJARAN LITERASI KELOMPOK A DI ERA PANDEMI COVID-19 - Jawharah Qalby, Dian; Hapidin, Hapidin; Juniasih, Indah (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2023)
This study aims to describe the Teacher's Strategy in Learning Literacy Group A at TK Aisyiyah 21 Rawamangun which is a sekolah penggerak and the learning is carried out using blended learning. This study uses a descriptive method in group a in TK Aisyiyah 21 Rawamangun. Data collection procedures were carried out by means of observation, interviews, and documentation. Data analysis uses data reduction, data display, and data verification. Data checking is done by triangulation. The findings of the research show that the objectives of literacy learning are to develop reading, listening, speaking, and writing skills in the form of writing and pictures, developing good character, critical thinking skills, arithmetic and problem solving. The process of activities that take place in literacy learning are literacy activities that are integrated into the theme and the development of the theme is already in the form of a theme project that produces work. The methods used are lecturing, question and answer, singing, telling stories, and habituation. The media used are books, letter cards, word cards, literacy trees, talking dolls, smart boards, youtube videos, songs, worksheets, props, and media made by teachers such as pizza puzzles, attaching ropes, and others. The material provided is based on the ongoing theme. Evaluation is carried out by observing children during learning, testing children one by one, evaluating portfolios, and viewing learning records. The research findings have their respective advantages online and offline.